2011
DOI: 10.1186/1556-276x-6-94
|View full text |Cite
|
Sign up to set email alerts
|

A cylindrical core-shell-like TiO2 nanotube array anode for flexible fiber-type dye-sensitized solar cells

Abstract: A versatile anodization method was reported to anodize Ti wires into cylindrical core-shell-like and thermally crystallized TiO2 nanotube (TNT) arrays that can be directly used as the photoanodes for semi- and all-solid fiber-type dye-sensitized solar cells (F-DSSC). Both F-DSSCs showed higher power conversion efficiencies than or competitive to those of previously reported counterparts fabricated by depositing TiO2 particles onto flexible substrates. The substantial enhancement is presumably attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…If such tubes are used together with an appropriate TiCl 4 treatment, efficiencies up to 8.14 % can be achieved. 217 Another simple approach to improve geometry factors is growing nanotubes on already structured metal substrates such as Ti metal wire, mesh and bifacial (TiO 2 nanotubes grown on both metal surfaces) substrate [645][646][647][648][649][650][651][652] . Such structures may provide higher specific surface area than TiO 2 nanotubes on flat metal substrate.…”
mentioning
confidence: 99%
“…If such tubes are used together with an appropriate TiCl 4 treatment, efficiencies up to 8.14 % can be achieved. 217 Another simple approach to improve geometry factors is growing nanotubes on already structured metal substrates such as Ti metal wire, mesh and bifacial (TiO 2 nanotubes grown on both metal surfaces) substrate [645][646][647][648][649][650][651][652] . Such structures may provide higher specific surface area than TiO 2 nanotubes on flat metal substrate.…”
mentioning
confidence: 99%
“…Such fabrication advances have also been shown to address challenges associated with treating conditions such as bone cancer, infection and inflammation, as 'in-bone' therapeutic implants [59]. Yu et al in 2011 reported TNT fabrication on Ti wires, followed by complete dissolution of wire core; thus yielding loose core-shell TNT structures [53]. The novel TNT structures in this study were proposed as photo-anodes for solar-cell application.…”
Section: Substrate Choicementioning
confidence: 91%
“…These include Ti wires, hollow tubes, meshes etc., which are proposed for various applications [53][54][55][56]. Being able to use a range of shapes of Ti substrate for fabricating TNTs opens a new window for integration of the technology into established medical implant devices.…”
Section: Substrate Choicementioning
confidence: 99%
“…In the DSSC research, interfacial surface passivation was extensively investigated for the TCO and metal foil substrates, with only few reports on metallic wires [11,12]. In our previously reported metal wire based novel cylindrical TCO-less DSSC (C-DSSC) [9] we discussed its advantages over the previous cylindrical architectures and the effect of different metal wire characteristics on the solar cell performance.…”
Section: Introductionmentioning
confidence: 98%
“…In such metallic substrate based photoanode, the photo generated electron transfer from TiO 2 to the conducting surface is one of the major controlling factors to achieve high power conversion efficiency (PCE). To improve this electron transfer process, great deal of the attempts such as introduction of interfacial layers on the Ti and stainless steel (SS) foils [10][11][12][13][14][15] have been made in order to provide a better binding force to the TiO 2 nanoparticle and smooth untreated metallic substrates.…”
Section: Introductionmentioning
confidence: 99%